2022
DOI: 10.1038/s41598-022-10431-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on patients with chronic pain seeking care at a tertiary pain clinic

Abstract: Empirical data on the health impacts of the COVID-19 pandemic remain scarce, especially among patients with chronic pain. We conducted a cross-sectional study matched by season to examine patient-reported health symptoms among patients with chronic pain pre- and post-COVID-19 pandemic onset. Survey responses were analyzed from 7535 patients during their initial visit at a tertiary pain clinic between April 2017–October 2020. Surveys included measures of pain and pain-related physical, emotional, and social fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
2
15
0
1
Order By: Relevance
“…It is therefore possible that orthopaedic patients in our practice experienced a similar trend in physical and mental health, with patients already recovered to prepandemic levels by 2021. Similar to our results, a cross-sectional study of patients with chronic pain presenting to a tertiary pain clinic in the California Bay area found that although pain catastrophizing scores were elevated when COVID-19 peaked in July 2020, physical function, pain interference, depression, and anxiety scores were either improved or unchanged compared with the pre-COVID-19 cohort [34]. The authors contributed these findings, in part, to patients in the post-COVID-19 cohort reporting increased access to emotional support and no worsening changes in social isolation and satisfaction with social roles.…”
Section: Differences In Promis Scores Between Before and During The P...supporting
confidence: 88%
“…It is therefore possible that orthopaedic patients in our practice experienced a similar trend in physical and mental health, with patients already recovered to prepandemic levels by 2021. Similar to our results, a cross-sectional study of patients with chronic pain presenting to a tertiary pain clinic in the California Bay area found that although pain catastrophizing scores were elevated when COVID-19 peaked in July 2020, physical function, pain interference, depression, and anxiety scores were either improved or unchanged compared with the pre-COVID-19 cohort [34]. The authors contributed these findings, in part, to patients in the post-COVID-19 cohort reporting increased access to emotional support and no worsening changes in social isolation and satisfaction with social roles.…”
Section: Differences In Promis Scores Between Before and During The P...supporting
confidence: 88%
“…The threat of the virus in combination with restrictions and quarantines has been associated with increased rates of anxiety, depression, stress, and decreased well-being [ 1 , 2 , 3 , 4 ]. In parallel, self-reported pain increased [ 5 , 6 , 7 ], especially when patients suffering from chronic pain did not have access to treatment [ 8 ], suggesting that adequate clinical care can prevent pain augmentation during a pandemic [ 9 , 10 ]. Further, self-reported pain during the pandemic was associated with decreased physical activity and increases in psychological stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there was much uncertainty, lockdowns, and physical distancing, Australia avoided significant impacts 1 seen in other countries, where large numbers of severe cases and deaths were experienced. 52 Lockdowns varied by state and sometimes by local area within states and territories; however, during wave 2 data collection period, most jurisdictions were coming out of the first major lockdown and restrictions were easing.…”
Section: Methodsmentioning
confidence: 99%